2007
DOI: 10.1590/s1415-47572007000600012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the DGAT1 gene in the Indian buffalo (Bubalus bubalis)

Abstract: The positional candidate diacylglycerol O-acyltransferase (DGAT1) gene affecting milk fat percentage is reported in Indian buffaloes (Bubalus bubalis). A comparison with Chinese buffalo (Bubalus bubalis) revealed eight exonic single nucleotide polymorphisms (SNPs), five of which were non-synonymous. A total of 19 SNPs were observed among diverse buffalo breeds in India. A Unique 22 base insertion has been reported in the intron between exon ten and eleven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Several studies reported single nucleotide polymorphisms (SNPs) in the buffalo DGAT1 gene (Tantia et al 2006;Mishra et al 2007;Raut et al 2012;Venkatachalapathy et al 2013, Cardoso et al 2015. Some studies showed the influence of SNPs in production traits in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported single nucleotide polymorphisms (SNPs) in the buffalo DGAT1 gene (Tantia et al 2006;Mishra et al 2007;Raut et al 2012;Venkatachalapathy et al 2013, Cardoso et al 2015. Some studies showed the influence of SNPs in production traits in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…The allele frequencies of the two SNPs at the DGAT1 gene in three buffalo breeds are given in online Supplementary Table S2. Mishra et al (2007) reported 13 SNPs by comparing the DGAT1 exons sequences of the Chinese buffalo (2n = 48) and Indian buffalo (2n = 50), which may due to the difference in the genetic evolution of the DGAT1 in the Riverine buffalo and the swamp buffalo. Moreover, all three buffalo groups shared the same K genotype with K232A mutation in the 8th exon of DGAT1 , which is a well-recognized mutation related to milk fat and protein percentages (Spelman et al 2002; Naslund et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Buffalo play an important role in the rural economy of developing countries. In addition to the utility of these animals for milk and meat production, their adaptation to natural conditions and tolerance to diseases makes them economically advantageous (Aytekin et al, 2011;Mishra et al, 2007;Yilmaz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Buffalo genetic resources are depleting and the loss of some genotypes may jeopardize the continuation of the species (Aytekin et al, 2011;Gargani et al, 2009;Mishra et al, 2007;Soysal et al, 2005;Yilmaz et al, 2011). For this reason, the Anatolian Water Buffalo are involved in a protection program of gene resources with the declaration of guidelines for subsidizing animal farming (Prescript no: 2006/9) by the Ministry of Agriculture and Rural Affairs in Turkey.…”
Section: Introductionmentioning
confidence: 99%